Motivasi Generasi Muda Terhadap Sektor Pertanian di Desa Karangpatihan Ponorogo - Dian Elys Safitri; Ratna Yunita (Niqosiya: Journal of Economics and Business Research, 2026)
Introduction: Agriculture is an important economic sector that provides food and employment opportunities, particularly in rural areas. However, the declining interest of the younger generation in agriculture has created challenges for farmer regeneration. Despite this condition, some rural youth continue to engage in the agricultural sector. Therefore, this study aims to examine the motivation of young people to remain involved in the agricultural sector and identify the factors influencing their participation in Karangpatihan Village, Pulung District, Ponorogo Regency. Research Method: This study employed a qualitative research method. Data were collected through interviews, observations, and documentation involving young people engaged in the agricultural sector. The data were analyzed descriptively to understand the motivations and influencing factors behind youth involvement in agriculture. Results: The findings show that young people remain involved in the agricultural sector because agriculture is perceived as a legitimate source of income that can fulfill family needs. In addition, flexible working hours and feelings of satisfaction and peace while working in agriculture strengthen their motivation. The existence of middlemen also facilitates crop marketing and provides capital support, increasing youth interest in agriculture. Furthermore, the motivation of the younger generation is influenced by cultural factors, such as farming traditions passed down through generations within the family; social factors, including rural environments dominated by agricultural land and limited employment opportunities; and psychological factors, such as pride, self-confidence, satisfaction, and comfort in agricultural work. Conclusion: This study concludes that the agricultural sector continues to be viewed by rural youth as a viable source of livelihood that provides economic, social, and psychological benefits. Cultural, social, and psychological factors play significant roles in encouraging the younger generation to remain involved in the agricultural sector.